Experiences of persons in COVID-19 institutional quarantine in Uganda: a qualitative study - Ndejjo, Rawlance; Naggayi, Gloria; Tibiita, Ronald; Mugahi, Richard; Kibira, Simon P. S. (BMC public health, 2021)
Background Quarantine has been adopted as a key public health measure to support the control of the Coronavirus disease (COVID-19) pandemic in many countries Uganda adopted institutional quarantine for individuals suspected of exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to be placed in institutions like hotels and/or hostels of institutions for at least 14 days. This study explored experiences of individuals who underwent institutional quarantine in Uganda to inform measures to increase its effectiveness and reduce its associated negative impact. Methods We conducted a qualitative description study using in-depth interviews with 20 purposively selected individuals who had spent time in institutional quarantine facilities. These were mainly phone-based interviews that were audio recorded and transcribed verbatim. Electronic data coding was conducted using Atlas.ti 7 software. Thematic content analysis was used to synthesize the findings with similar codes grouped to form sub-themes and ultimately study themes. The findings are presented thematically with typical participant quotes. Results Study participants spent between 14 to 25 days in institutional quarantine. Four themes emerged describing the experiences of study participants during institutional quarantine, which determined whether participants’ experiences were positive or negative. These themes were: quarantine environment including facility related factors and compliance with COVID-19 measures; quarantine management factors of entity paying the costs, communication and days spent in quarantine; individual factors comprising attitude towards quarantine, fears during and post-quarantine and coping mechanisms; and linkage to other services such as health care and post-quarantine follow-up. Conclusion The planning, management and implementation of the quarantine process is a key determinant of the experiences of individuals who undergo the measure. To improve the experience of quarantined individuals and reduce its associated negative impact, the pre-quarantine process should be managed to comply with standards, quarantined persons should be provided as much information as possible, their quarantine duration should kept short and costs of the process ought to be minimised. Furthermore, quarantine facilities should be assessed for suitability and monitored to comply with guidelines while avenues for access to healthcare for the quarantined need to be arranged and any potential stigma associated with quarantine thoroughly addressed.